Pelvic organ prolapse surgery in Western Australia: A population-based analysis of trends and peri-operative complications - Hunt, F.; Holman, C.; Einarsdottir, K.; Moorin, Rachael; Tsokos, N. (Springer International, 2013)
Introduction and hypothesis: We previously described a declining rate of surgery in the treatment of pelvic organ prolapse (POP) in Western Australia. This paper builds on previous work by examining temporal trends and the post-operative risk of in-hospital complications, following first time incident prolapse surgery in a population-based cohort of women. Methods: We investigated rates of prolapse surgery between 1988 and 2005 according to age group and concomitant procedure type for 34,509 women whose data were extracted from the WA Data Linkage System. We investigated changes over time in the demographic characteristics of women undergoing surgery and whether the presence of selected concomitant procedures increased the risk of in-hospital complications. Results: During the study period, 34,509 women underwent an incident surgery for POP. Concomitant hysterectomy was performed in more than half of all surgeries (52.4 %) and a concomitant urinary incontinence (UI) surgery was noted in 25.8 %. 10.9 % of patients experienced a complication of interest, with the highest percentage of complications recorded in women who underwent multi-concomitant surgery. After controlling for age, comorbidity and time period we found that concomitant UI surgery increases in-hospital complications (OR 1.61 95 % CI 1.42–1.83) only in women who have a repair procedure (colporrhaphy and/or enterocele repair). There was no significant effect of concomitant procedures in women who underwent a combined repair and apical prolapse procedure. Conclusions: Surgery to treat prolapse is common, has low mortality and concomitant surgery only increases complications when combined with simpler prolapse surgery.